Deferring the Familial Default: The Transnational Turn in Nancy Huston's Lignes de faille. Issue 3 (December 2018) - Rice, Alison
Abstract : Nancy Huston's Lignes de faille, recipient of the Prix Femina in 2006, was one of five literary works mentioned at the outset of a collectively signed document published in March 2007 in Le Monde . Titled 'Pour une littérature-monde en français', this manifesto claimed to identify a revolution in French-language literature, lauding the fact that a variety of works by writers from diverse locations now represented 'the world'. It is not surprising that Lignes de faille figures in this text, for Huston's novel marked a new transnational orientation in an œuvre that was already rich and varied. Lignes de faille moves to strategic places around the globe to tell the tale of a family whose displacements have led to traits and troubles that have been transmitted across continents and generations, suggesting that while national roots may not cling to us, hereditary ones may be deferred, but not, in the end, denied.